Capillary trapping quantification in sandstones using NMR relaxometry - Connolly, P.; Vogt, S.; Iglauer, Stefan; May, E.; Johns, M. (Wiley-Blackwell Publishing, Inc., 2017)
© 2017. American Geophysical Union. All Rights Reserved. Capillary trapping of a non-wetting phase arising from two-phase immiscible flow in sedimentary rocks is critical to many geoscience scenarios, including oil and gas recovery, aquifer recharge and, with increasing interest, carbon sequestration. Here we demonstrate the successful use of low field 1 H Nuclear Magnetic Resonance [NMR] to quantify capillary trapping; specifically we use transverse relaxation time [T 2 ] time measurements to measure both residual water [wetting phase] content and the surface-to-volume ratio distribution (which is proportional to pore size] of the void space occupied by this residual water. Critically we systematically confirm this relationship between T 2 and pore size by quantifying inter-pore magnetic field gradients due to magnetic susceptibility contrast, and demonstrate that our measurements at all water saturations are unaffected. Diffusion in such field gradients can potentially severely distort the T 2 -pore size relationship, rendering it unusable. Measurements are performed for nitrogen injection into a range of water-saturated sandstone plugs at reservoir conditions. Consistent with a water-wet system, water was preferentially displaced from larger pores while relatively little change was observed in the water occupying smaller pore spaces. The impact of cyclic wetting/non-wetting fluid injection was explored and indicated that such a regime increased non-wetting trapping efficiency by the sequential occupation of the most available larger pores by nitrogen. Finally the replacement of nitrogen by CO 2 was considered; this revealed that dissolution of paramagnetic minerals from the sandstone caused by its exposure to carbonic acid reduced the in situ bulk fluid T 2 relaxation time on a timescale comparable to our core flooding experiments. The implications of this for the T 2 -pore size relationship are discussed.